KONTEKS RELIGIO-POLITIK PERKEMBANGAN SUFISME: Telaah Konsep Mahabbah dan Ma’rifah - Jinan, Mutohharun (Universitas Muhammadiyah Surakarta, 2017)
This paper discusses the essence of the concepts of Sufism (Sufism) mahabbah and ma'rifah and how and in what context the concepts of Sufism are formulated. These two concepts are the teachings of Sufism from three Sufi figures namely Rabi'ah al-Adawiyah, Zunnun al-Mishri and al-Gahazali. Can be concluded that the three Sufis in laying the foundations of Sufism teachings did not escape from the context of his time. Rabi'a and Zunnun both live in situations where people are busy taking care of the exoteric things that do not penetrate to the esoteric dimensions of Islam. Both have shifted from the paradigm of worship held by Muslims of his day, from fear of God to love to God. While al-Ghazali lives in a state of contradiction between various Islamic groups. Mahabbah and ma'rifah taught by the three Sufis is the implementation of piety in the process of truth-seeking encompassing plurality and cosmopolitanism in a phase of civilization.Makalah ini membahas hakikat konsep-konsep tasawuf (sufisme) mahabbah dan ma’rifah dan bagaimana dan dalam konteks apa konsep-konsep tasawuf itu dirumuskan. Kedua konsep ini merupaka ajaran tasawuf dari tiga tokoh sufi yaitu Rabi’ah al-Adawiyah, Zunnun al-Mishri dan al-Gahazali. Dapat disimpulkan bahwa ketiga sufi dalam meletakkan dasar-dasar ajaran tasawuf tidak luput dari konteks zamannya. Rabi’ah dan Zunnun sama-sama hidup dalam situasi dimana umat sibuk mengurus hal-hal yang sifatnya eksoteris yang tidak menembus pada dimensi esoteris Islam. Keduanya telah menggeser dari paradigma ibadah yang dipegangi oleh umat Islam di zamannya, dari takut kepada Allah menjadi cinta kepada Allah. Sedangkan al-Ghazali hidup dalam keadaan pertentangan antar berbagai golongan Islam. Mahabbah dan ma’rifah yang diajarkan oleh ketiga sufi merupakan implementasi kesalehan dalam proses pencarian kebenaran yang dilingkupi pluralitas dan kosmopolitanisme dalam suatu fase peradaban.